Study some of inflammatory indicator with corona patient and relation with chronic disease - Amer, Fatma; Ahmid, Dhea Sadi; lateef, Abada Ali (Technium BioChemMed, 2022)
The coronavirus disease epidemic of 2019 (COVID-19) is a scientific, medical, and societal problem.in modern study the investigation of viral pathogenetic pathways, as well as cellular and organ damage, involves the implementation of novel biomarkers. The study showed increased of level of sugar in a significant relationship between patients with COVID-19 and patients with diabetes mellitus at P>0.01, On the other hand, the study demonstrated an increase in the rate of D - dimer in patients infected with Covid - 19,.as well as the rate of some inflammatory markers such as acute phase protein(CRP) and WBC at P>0.05 ,The following chemical makers LDH ,ferritin) significantly higher levels in COVID-19-infected individuals than in the Control group. Screening, clinical treatment, and major complication prevention would all benefit from effective biomarkers.